β-Lapachone Selectively Kills Hepatocellular Carcinoma Cells by Targeting NQO1 to Induce Extensive DNA Damage and PARP1 Hyperactivation - Zhao, Wenxiu; Jiang, Lingxiang; Fang, Ting; Fang, Fei; Liu, Yingchun; Zhao, Ye; You, Yuting; Zhou, Hao; Su, Xiaolin; Wang, Jiangwei; Liu, Sheng; Chen, Yaomin; et al. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death globally. Currently there is a lack of tumor-selective and efficacious therapies for hepatocellular carcinoma. β-Lapachone (ARQ761 in clinical form) selectively kill NADPH:quinone oxidoreductase 1 (NQO1)-overexpressing cancer cells. However, the effect of β-Lapachone on HCC is virtually unknown. In this study, we found that relatively high NQO1 and low catalase levels were observed in both clinical specimens collected from HCC patients and HCC tumors from the TCGA database. β-Lapachone treatment induced NQO1-selective killing of HCC cells and caused ROS formation and PARP1 hyperactivation, resulting in a significant decrease in NAD+ and ATP levels and a dramatic increase in double-strand break (DSB) lesions over time in vitro. Administration of β-Lapachone significantly inhibited tumor growth and prolonged survival in a mouse xenograft model in vivo. Our data suggest that NQO1 is an ideal potential biomarker, and relatively high NQO1:CAT ratios in HCC tumors but low ratios in normal tissues offer an optimal therapeutic window to use β-Lapachone. This study provides novel preclinical evidence for β-Lapachone as a new promising chemotherapeutic agent for use in NQO1-positive HCC patients.